استخدام الأسلوب الخطابي الفعّال في تعليم اللغة العربية للمبتدئين في نشاط صباح اللغة مبنى ام سلامة - Amin, Azkiya Rafida (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the effectiveness of using the rhetorical method (uslūb khuṭābī) in teaching Arabic to beginners through the "Shobahul Lughoh" (Language Morning) activity at Umm Salamah dormitory, part of the Sunan Ampel Al-Aly Institute at the State Islamic University of Maulana Malik Ibrahim Malang. The study employs a qualitative descriptive approach, utilizing observation, interviews, and documentation as data collection techniques from thirty beginner-level female students. The results reveal that the rhetorical method significantly contributes to improving vocabulary acquisition and boosting students’ confidence in speaking Arabic, especially when vocabulary is delivered clearly and repeatedly. Furthermore, practical application of this method in activities such as the “International Language Day” enhances comprehension and real-life usage of the language. However, the effectiveness of this method is affected by several obstacles, including the early execution time, lack of variety in activities, and low self-confidence among some students. The study recommends improvements in the method's implementation, including diversifying learning activities and adjusting the schedule, to create a more engaging and effective learning environment for beginners.